Correction to: Deep learning-based reconstruction improves the image quality of low-dose CT enterography in patients with inflammatory bowel disease. - He, Weitao; Xu, Ping; Zhang, Mengchen; Xu, Rulin; Shen, Xiaodi; Mao, Ren; Li, Xue-hua; Sun, Can-hui; Zhang, Ruo-nan; Lin, Shaochun (Abdominal Radiology, 2025)
A correction notice was issued for an article titled "Deep learning-based reconstruction improves the image quality of low-dose CT enterography in patients with inflammatory bowel disease" in the journal Abdominal Radiology. The correction added a note acknowledging equal contributions from Weitao He, Ping Xu, and Mengchen Zhang. The original article has been updated to reflect this correction. The publisher, Springer Nature, maintains neutrality regarding jurisdictional claims and institutional affiliations.